Lisbon's unsustainable tourism intensification: contributions from social representations to understanding a depoliticised press discourse and its consequences - Boager, E. (2021)
Resistance to tourism intensification and its unsustainability has grown. However, decision-makers in many cities continue to present tourism and the political and legislative options supporting it as an inevitable and consensual path for economic growth, concealing competing choices, voices, and values. The media can follow, presenting the issue in a depoliticised way: i.e., by foregrounding undiscussed dominant discourses, leaving little space for debate of alternatives. Drawing from Social Representations Theory and the literature on depoliticisation, we offer an integrative theoretical and methodological proposal for analysing tourism discourses in the press, as a privileged arena where meanings are constructed and contested. Specifically, we explore if and to what extent the Portuguese press presenting Lisbon's tourism intensification (2011–2017) foregrounded undiscussed (depoliticised) and hegemonic representations. A content analysis (n = 247 articles; four newspapers) identifies signs of a hegemonic and depoliticised tourism's view, with low heterogeneity of voices and values. Second, a detailed discursive analysis (n = 187; two newspapers) illustrates discursive strategies helping advance (propaganda and reification) or dispute (propagation and consensualization) this view. Contributions to the understanding of neoliberalism's discursive formations and its contestations made concrete around tourism are discussed, with implications for future tourism more attentive to justice and participation issues.